Mathematical Model of Landslides with Curved Sliding Plane Using Fracture Criterion of Solid Soil-Rock System - Ikah Ning Prasetiowati Permanasari; Lilik Hendrajaya; Gunawan Handayani (Science and Technology Indonesia, 2022)
Alluvial cliff with high slope and step has been known to cause curving sliding plane. This phenomenon is adopted as a knowledge, but it has never been studied theoretically. In this paper, mathematics derivation phenomenon is proposed using special model of 11 fracture criterion ????-????. The quantity of ???? is A???? 2 with A is a friction coefficient of stress ???? 2 . The failure model was substituted to the corresponding Mohr circle resulting the expected curve. The curve was used to measure the observed field profile to obtain the friction coefficient A.